A Constant Recontracting Model of Sovereign Debt - Bulow, Jeremy; Rogoff, Kenneth (Journal of Political Economy, 1989)
Few sovereign debtors have repudiated their obligations entirely. But despite the significant sanctions at the disposal of lenders, many borrowers have been able to consistently negotiate for reduced repayments. This paper presents a model of the on-going bargaining process that determines repayment levels.